A comparison of likelihood ratios obtained from EuroForMix and STRmix™. Issue 6 (22nd September 2021) - Cheng, Kevin; Bleka, Øyvind; Gill, Peter; Curran, James; Bright, Jo‐Anne; Taylor, Duncan; Buckleton, John
Abstract: Likelihood ratios ( LR ) differences between the probabilistic genotyping software EuroForMix and STRmix™ are examined. After considering differences in the allele probabilities, the LRs from both software for an unambiguous single‐source profile were identical (four significant figures). LRs from both software for an unambiguous single‐source profile with alleles previously unseen in the allele frequency database (rare alleles) were the same (three significant figures) for θ = 0.01. Due to differences in the minimum allele frequencies, the LR s differed by three orders of magnitude when θ = 0. For both software, the LR s for a single‐source dilution series decreased as the input amount decreased. The LR s from both software were within an order of magnitude for known contributors. The largest difference was where the target input amount was 0.0156 ng: The LR EuroForMix was 2.1 × 10 25 and the LR STRmix was 8.0 × 10 24 . Both software show similar LR behavior with respect to mixture ratio. For two person mixtures the LR increases for both the major and the minor as the ratio moves away from 1:1. The LR for the major stabilizes at about 3:1 whereas the LR for the minor reaches its maximum at about 3:1 and then declines. Greater differences in LR were observed between EuroForMix and STRmix™ for mixtures. One‐hundred and twenty‐nine mixtures from the PROVEDIt dataset were compared. LR s for 84% of the comparisons for known contributors without rare alleles were within two orders of magnitude. Five divergent results were investigated, and a manual intervention approach was applied where appropriate.